Effect of extracorporeal photopheresis on lung function decline for severe bronchiolitis obliterans syndrome following allogeneic stem cell transplantation. Issue 4 (29th May 2015) - Brownback, Kyle R.; Simpson, Steven Q.; Pitts, Lucas R.; Polineni, Deepika; McGuirk, Joseph P.; Ganguly, Siddhartha; Aljitawi, Omar S.; Lin, Tara L.; Singh, Anurag; Abhyankar, Sunil
Abstract : Extracorporeal photopheresis (ECP) is a commonly used treatment for severe graft‐versus‐host‐disease (GVHD). We sought to evaluate the effects of ECP over a prolonged period on forced expiratory volume in 1 s (FEV1) in patients with pulmonary GVHD. We identified eight patients who developed new airflow obstruction following allogeneic stem cell transplantation and a substantial decline in FEV1 despite receiving corticosteroids and standard therapy for pulmonary GVHD. Those eight patients were treated with ECP for a period of 1 year, with a primary endpoint of FEV1 change during this treatment period. Over the first 3 months of ECP, there was no further decline in FEV1 in seven of the eight patients. However, over the 1 year period, only two of the eight patients had stability in FEV1. The rate of FEV1 decline was substantially less once ECP was initiated, though the median FEV1 continued to decline over 1 year of therapy. All patients survived through the first year of ECP therapy. There was a significant decrease in the median dose of prednisone per patient throughout the 12 months of ECP treatment. ECP shows promise in slowing rate of decline of FEV1 in pulmonary GVHD, though the effects may not be long lived. J. Clin. Apheresis 31:347–352, 2016. © 2015 Wiley Periodicals, Inc.